If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-9x + 11) * 8 = 0 Reorder the terms: (11 + -9x) * 8 = 0 Reorder the terms for easier multiplication: 8(11 + -9x) = 0 (11 * 8 + -9x * 8) = 0 (88 + -72x) = 0 Solving 88 + -72x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-88' to each side of the equation. 88 + -88 + -72x = 0 + -88 Combine like terms: 88 + -88 = 0 0 + -72x = 0 + -88 -72x = 0 + -88 Combine like terms: 0 + -88 = -88 -72x = -88 Divide each side by '-72'. x = 1.222222222 Simplifying x = 1.222222222
| 3z^3+6z^2=72z | | 1/3X-1-1/4X+2=3 | | 23=11x+1 | | 9=-2x+4 | | 7(p+1)=p-9 | | C=3.14(5) | | -5/6f+1=-4 | | 12-2A-2B=0 | | 5+-26=18x | | 2=15x | | (x+8)(x-3)+30=0 | | 52=4x-4 | | -4/6f+1=-4 | | 7u+9u+u=140 | | 7y-2=13+10 | | 4z-2=2+7 | | 4x-9=6r-13 | | 7x=5x-18 | | 9mn+p=2k | | 10/2+1=6 | | -8(x+9)=-96 | | b^2+6b-x^2+9=0 | | 5=4x+4 | | p/2+1=6 | | -91=-7(x+2) | | 6x+20=34 | | -2y-7=-13 | | 7b+12=31b | | 4(-0.4+-0.29)-3y=-13 | | 8x+22=-28 | | -6x+(7x+2)-(x-9)=19 | | |3x-8|-|3x-2|=6 |